Seismic performance assessment of adjacent building structures connected with superelastic shape memory alloy damper and comparison with yield damper. Issue 5 (18th January 2022) - Gur, Sourav; Roy, Koushik; Singh, Pranay
Summary: The use of supplemental damping for mitigation of seismic hazard of adjacent building structures is proven to be a practical and efficient way. In developing an efficient damper/energy absorber, shape memory alloy (SMA) material is an excellent candidate due to its well‐known high‐energy dissipation capacity via thermomechanical‐phase transformation. For the first time, the present study focuses on the seismic response control efficiency of superelasticity SMA damper over conventional yield damper, for vibration control of adjacent building structures. To this end, the response of two adjacent steel building frame structures connected with SMA and yield dampers is evaluated through nonlinear dynamic time‐history analysis, under a set of recorded near‐fault ground motions. Optimal characteristics of both dampers are obtained through a parametric study. The robustness of the improved performance of the SMA damper over the yield damper is studied for various characteristic damper strengths, building structures, as well as different scenarios of seismic loading. It is being demonstrated that the superelasticity SMA damper significantly improves the floor displacement control efficiency over the yield damper and also provides a considerable amount of reduction in the peak value of the absolute floor acceleration.